SKELETAL ANCHORAGE IN ORTHODONTIC TREATMENT OF A CLASS II MALOCCLUSION - Andreea Păun; Radu Stanciu; Ion Pătrașcu (Romanian Society of Oral Rehabilitation, 2015)
Aim of the study The aim of this paper is to present a clinical case of an Angle class II malocclusion which was treated with premolar extractions and skeletal anchorage in order to establish the facial and dental balance. Material and methods After the clinical and paraclinical evaluations, it was assigned a diagnostic of a class II, division 2 malocclusion according to Angle classification. The main objective of the orthodontic treatment was maintaining the anchorage after premolar extractions which was obtained with the aid of mini-implants. Results The orthodontic treatment managed to restore the functionality of the occlusion and to enhance facial aesthetics. Conclusions The skeletal anchorage with orthodontic mini-implants provided the high needs of anchorage necessary for managing the space obtained after extractions.